Innovation Strategy Through Corporate Entrepreneurship: A Literature Review - Adhi Bawono, Isanawikrama, Abdullah Umar, Hariyatno (International Journal of Advanced Science and Technology, 2020)
It is required a mindset and entrepreneurial activity in the business. Corporate entrepreneurship is an effective way of stimulating innovation, revitalizing organizations, and increasing productivity. Innovation is needed for a corporation in the competition nowadays. It is not easy to support an entrepreneurial environment in the corporation. This research provides some preliminary insight into the scholar who intends to investigate corporate entrepreneurship. The success factor of corporate entrepreneurship implementation as a foundation for implementing a corporate innovation strategy is tried to discover by this paper. The research using a systematic literature review, the searching process resulted in 963 papers by using the keyword “corporate entrepreneurship” and “innovation” published after 2012. The relevant papers’ title defined as “candidate studies”. The process of the selection has result in 121 articles to be reviewed from the article collected to “candidate studies”. Then, these articles were then re-elected by reviewing the abstract to address the research question. After studied further, there are only 36 papers that can be used in this research. The final results reveal important indicators in the corporate entrepreneurship based on the conclusions of previous studies.